Low Tropospheric Ozone Over the Indo‐Pacific Warm Pool Related to Non‐Electrified Convection - Clara M. Nussbaumer; Andrea Pozzer; Michael Hewson; Linda Ort; Bianca Krumm; Joseph Byron; Jonathan Williams; Philipp Joppe; Florian Obersteiner; Andreas Zahn; Jos Lelieveld; Horst Fischer (Geophysical Research Letters)
Abstract Lightning is the most important source of nitric oxide (NO) in the tropical upper troposphere and controls the formation of tropospheric ozone (O3). It is associated with deep convection and occurs mostly over continents. The Chemistry of the Atmosphere Field Experiment in the Pacific (CAFE Pacific) was conducted in early 2024 from Cairns, Australia, taking airborne measurements across the Australian continent and the surrounding maritime regions. Based on cloud top properties, lightning data and in situ observations of NO, O3 and carbon monoxide, we show that deep convection occurs over Northern Australia and the Indo‐Pacific Warm Pool. While we identify strong lightning activity over Australia, we observe deep convection in the Warm Pool that is not electrified. Our observations of low O3 in the Warm Pool can be attributed to O3‐poor air from the marine boundary layer, which is not replenished by photochemical production from NO at high altitudes.